Digital Press Criticism: The Symbolic Dimensions of Donald Trump's Assault on U.S. Journalists as the "Enemy of the People". Issue 6 (3rd July 2021) - Carlson, Matt; Robinson, Sue; Lewis, Seth C.
Abstract: Digital press criticism, or the use of non-journalistic platforms as a means for critiquing journalism, is made possible by digital technologies that circumvent traditional media channels. This form of criticism is not marginal, but indeed is increasingly central within the political communication environment. This can be seen in President Donald Trump's persistent attacks on U.S. journalists. This article examines how journalists responded to two episodes of digital press criticism, in 2017 and 2019, when Trump used Twitter to affix the incendiary label of "enemy of the people" to journalists. This article explores the propensity of the journalistic community to use frames that individualize Trump by promoting his agency as paramount. We argue that this framing obscures and downplays, if not outright ignores, how far-right politicians utilize emergent channels of digital press criticism to undermine journalism's epistemic legitimacy and raise questions about its social role.